Proinsulin Expressing Neuroendocrine Tumors of the Pancreas: An Underrecognized Entity. Issue 1 (January 2019) - Celli, Romulo; Tang, Laura H.; Cai, Guoping; Freedman-Weiss, Mollie; Colunga, Monica; Salem, Ronald R.; Majumdar, Sachin; Jain, Dhanpat
Abstract : Objectives: Rare cases of pancreatic neuroendocrine tumors (PNETs) that produce only proinsulin (PI) and manifest with hypoglycemia have been reported. Proinsulin expression in PNET has not been systematically studied, and the clinicopathologic features of such tumors remain unknown. Methods: We studied expression of PI by immunohistochemistry (IHC) in 136 PNETs from 2 high-volume surgical oncology centers and assessed all available clinicopathologic data. Results: Thirty-six (26%) of PNETs were positive for PI by IHC, most (89%) of which coexpressed insulin IHC. Nine PI-positive tumors represented functional insulinomas. Patients with PI IHC–positive tumors demonstrated significantly lower mean preoperative serum glucose compared with PI-negative PNET patients, even when insulinomas were excluded. No differences in survival between PI IHC–positive and PI IHC–negative tumors were observed. We identified 2 PI-positive PNETs from hypoglycemic patients, which were not insulinomas or other functional variants and in which serum PI was never tested. These may have been undetected proinsulinomas. Conclusions: Proinsulin-expressing PNETs (functional or non) are not uncommon. Patients who present with hypoglycemia and normal insulin levels should be screened for proinsulinoma. Proinsulin IHC could also be used to screen for proinsulinoma. To further elucidate the clinical significance of PI expressing PNETs, prospective studies are required.